Using a modified online jigsaw technique to address covid-19 related topics during the pandemic lockdown. - Bill Anderson; Caroline Cudney (Journal of Effective Teaching in Higher Education)
In using the jigsaw technique (Aronson, 2021), groups are initially formed with each student having responsibility for one specific piece of information needed to complete the assignment. Next, expert groups of students with the same material are formed in order to explore their material and prepare to teach it to their peers. Finally, the original groups are reformed and students, each having a different piece of information, must work together to complete the assignment.